Electronic Properties of PbTe Si Hetrojunction - Adem, Kadhim A (Al-Nahrain Journal of Science, 2012)
In this paper a study of the effect of annealing temperature on the electrical properties of PbTe films prepared by thermal evaporation technique on Si wafer has been achieved. The electric properties of PbTe including d.c conductivity and Hall effect, from d.c measurement. It is found that the electrical activation energies Ea1 and Ea2 increase from 0. 175 eV to 0.24 eV and form 0.53 eV to 0.536 eV with the increase of annealing temperature from 323 k to 373 k. Hall measurements showed that all films are p-type. Electrical properties of PbTehetrojunction, fabricated by deposition of PbTe film on Si using thermal evaporation, include current (I) and voltage (V) characterizations under dark and illumination conditions and capacitance and voltage measurement at varying annealing temperatures. Capacitance (C) and voltage (V) characteristics showed that the fabricated diode type. The built in potential was determined by extrapolation of 1/C2-V curve. The built in potential (Vbi) for the PbTe Si System was found to be increase from 1.37eV to 1.65eV with increasing of annealing temperature.